Quem vai me ensinar de novo? Os homens se educam em comunhão: experiencias de constituição docente através de grupos de estudos de professores de história (2004-2006) - Marçal, Maria Antonia (2007)
This paper aims to comprehend the movement of autonomy of three experiences about teaching constitution in study groups of History teachers. The research methodology used was the research – action which is composed of registers in field journals, interviews, reports and recordings of the meeting which the author took part. Also, analysis and synthesis of the experiences data collected from talks with Education theorists especially the ones who are linked to Critical Pedagogy. This pedagogy is understood as the one centered in the valuation of the students experiences which are considered central in the capitalist society divided into classes and with asymmetric relations of power where the education happens. This theory considers the power of the teachers and the social transformation as something indispensable for the production of educational quality which cannot be separated from the political production in an open and fair society. The study groups were held in Ponta Grossa from 2004 to 2006. The first study group analyzed is the result of a partnership between the Regional Nucleus of Education of Ponta Grossa and the State University of Ponta Grossa. Id had a structure that prioritized the updating of teaching contents. Although the subjects who took part of it had an effective performance in the reflections, the professional trajectory of those teachers gave them sui generic characteristics once it was a group of teachers who invested in new history teaching methodologies. The second study group started in 2005 and it was idealized by the state secretary of education of Paraná. The study group showed different characteristics from the previous one. It was base don a model of teaching constitution which valued, with especial emphasis, the reading of proposed texts which were contrary to teachers´ knowledge and experiences. In this space of teaching constitution, the silence and distance were dominant and the proposed activities were simply done, but a movement of a severance made the teachers break the silence and share their experiences and trajectories at a point that a text about the Paraguay War mobilized their teaching knowledge. The third group analyzed in this paper was the study group “Stimulus to History Teachers Creativity” held from 2005 to 2006. It was idealized as a project of extension directly linked to this Masters research. In this space, it was aimed to create situations in which the exercise of teaching autonomy could be possible. It was put in evidence in certain moments especially in the acquisition of this space by its members, turning it into a cathartic space. Finally, it was observed the movement of a advance and retrocession of a teaching autonomy in these spaces, as well, it is possible to put in evidence that the process of construction of autonomy is a collective and individual process at the same time. The teachers feel the necessity of a collective space where they could share their experiences and anguish. On the other hand, the arrangement of the courses that a silence their knowledge doesn’t trigger off in the these subjects transforming actions in the education environment, if they don’t result of initiatives and/or the participants desire and if they don’t seize on the mechanisms of decision about the ways, rules and responsibility for their results.